If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5(2 + 3x) = 3x + 2(14 + 12x) + 8 2x + (2 * 5 + 3x * 5) = 3x + 2(14 + 12x) + 8 2x + (10 + 15x) = 3x + 2(14 + 12x) + 8 Reorder the terms: 10 + 2x + 15x = 3x + 2(14 + 12x) + 8 Combine like terms: 2x + 15x = 17x 10 + 17x = 3x + 2(14 + 12x) + 8 10 + 17x = 3x + (14 * 2 + 12x * 2) + 8 10 + 17x = 3x + (28 + 24x) + 8 Reorder the terms: 10 + 17x = 28 + 8 + 3x + 24x Combine like terms: 28 + 8 = 36 10 + 17x = 36 + 3x + 24x Combine like terms: 3x + 24x = 27x 10 + 17x = 36 + 27x Solving 10 + 17x = 36 + 27x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27x' to each side of the equation. 10 + 17x + -27x = 36 + 27x + -27x Combine like terms: 17x + -27x = -10x 10 + -10x = 36 + 27x + -27x Combine like terms: 27x + -27x = 0 10 + -10x = 36 + 0 10 + -10x = 36 Add '-10' to each side of the equation. 10 + -10 + -10x = 36 + -10 Combine like terms: 10 + -10 = 0 0 + -10x = 36 + -10 -10x = 36 + -10 Combine like terms: 36 + -10 = 26 -10x = 26 Divide each side by '-10'. x = -2.6 Simplifying x = -2.6
| -18-22=10x | | 14x=63-7x | | (x)2=200+(x-200)4 | | 4h-h=35+25 | | 7x-12y=4 | | -11x=3x-28 | | -2a^2+54a= | | (5+2x)*(3x-5)=0 | | -2a^2+54=0 | | 6x^3-17x^2+5x= | | -2a(a+27)=0 | | 4a^3+9a^2-4+2a^3-9a+9= | | 2x-8(7-x)=18 | | 22m+23=24m-25 | | x+-0.05x+1=n | | x+-0.05x+1= | | 7x+1=3(6x-7) | | 2s+6=s+13 | | 10x^2-6=7x | | x+-0.05x+1=1+11.95x | | (5-3x)(2+4x)= | | 6m+4=5m-1 | | -2[8-5(2-3x)-7x]=4(x+9) | | x+-0.05x+11.95x=1-1 | | X=(2x^2+3x-6)+(x^2-18x+6) | | 4x^2+3x-6=0 | | 6x^2-6x+10=2x^2-2x+25 | | x-0.5(0.1x-2)=1+11.95x | | -9x+3x=-24 | | 8x(3x+2)=-5(2-x)+3 | | 1270=.15x | | -5x-13x+3x=-25 |